Wildlife Trade Governance and Zoonosis: Missing Link From Forest to Market Place - Fajrini, Rika; Moore, Richard; Prameswari, Wendi; K Ghassani, Yumni; Phelps, Jacob (Department of Forest Resources Conservation and Ecotourism - IPB University, 2025)
Indonesia is a major hub for domestic and international wildlife trade. Illegal and unregulated trade threatens species survival and public health through potential zoonotic disease transmission. Effective governance, including strengthened legislation and enforcement, is essential to address these issues. This paper scrutinizes the laws and policies governing wildlife trade and zoonosis prevention in Indonesia, spotlighting the regulatory path from source to marketplace transactions. By analyzing existing regulations, both at the national and local levels, with a focus on Jakarta and Bandung as case studies for local regulation, this study aims to clarify the management of legal wildlife trade, the responsible actors, and their legal duties throughout the chain. The findings underscore a disconnect exists between upstream monitoring and downstream marketplace activities. Furthermore, the discussion reveals a critical regulatory loophole- the lack of regulations addressing standards for a healthy non-livestock wildlife market and the often-overlooked role of local government agencies, which, despite playing a marginalized role in wildlife trade monitoring strategies, are the forefront of zoonosis surveillance and monitoring duty.